Staphylococcus aureus aortitis and retroperitoneal fibrosis: A case report and literature review. (2016) - Yague, Marta; Temprano, Ignacio; Losa, Juan; De Benito, Luis; De La Cruz, Raul; Cheyne, Natalie; Henriquez, Cesar
Abstract: An infected aortic aneurysm is a process with high mortality rate. Survival is dependent on an early diagnosis and surgical management. This case report details a rare presentation of aortitis with persistent methicillin-sensitive Staphylococcus aureus (MSSA) bacteremia, which initially presented as retroperitoneal fibrosis and was ultimately fatal.